Production systems technology - Harms, Henry R (McGraw-Hill, 1992)
Thinking is the essence of being human. It is one of the things that makes you different from other animals. Some people believe that your brain stores information about every experience you have ever had in your life. This is what makes learning and remembering possible. What are you doing to fill your brain with information that will be useful to you in the future? Employers have been saying that the young people entering the workforce today do not have good thinking skills. They mean that these young people do not have the necessary skills for problem solving, for thinking creatively, for critical thinking, and for making decisions.; Quỹ Châu Á